2021
DOI: 10.3390/life11070636
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specific and Common Prostate Cancer Metastasis Genes as Suggested by Meta-Analysis of Gene Expression Data

Abstract: Anticancer therapies mainly target primary tumor growth and little attention is given to the events driving metastasis formation. Metastatic prostate cancer, in comparison to localized disease, has a much worse prognosis. In the work presented here, groups of genes that are common to prostate cancer metastatic cells from bones, lymph nodes, and liver and those that are site-specific were delineated. The purpose of the study was to dissect potential markers and targets of anticancer therapies considering the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…A recent publication that compared metastasis samples from the same primary but from different secondary sites showed that prostate cancer metastasis from bones, lymph nodes and liver differ substantially in transcription profiles, although a change in a group of genes is shared. Generally, changes in gene expression that were site-specific grouped in gene ontology terms that are reminiscent of processes that take place in the target organ (Samaržija, 2021). This is in line with the report that showed the induced expression of genes that are physiologically associated with liver function in liver metastases.…”
Section: Genomic and Transcription Profiles Of Metastatic Cells Show ...supporting
confidence: 82%
“…A recent publication that compared metastasis samples from the same primary but from different secondary sites showed that prostate cancer metastasis from bones, lymph nodes and liver differ substantially in transcription profiles, although a change in a group of genes is shared. Generally, changes in gene expression that were site-specific grouped in gene ontology terms that are reminiscent of processes that take place in the target organ (Samaržija, 2021). This is in line with the report that showed the induced expression of genes that are physiologically associated with liver function in liver metastases.…”
Section: Genomic and Transcription Profiles Of Metastatic Cells Show ...supporting
confidence: 82%
“…This approach appears promising based on the high number of genes with previous implications in PCa pathogenesis. For example, PCa patient EV expressed genes dysregulated or altered in PCa and/or metastasis (e.g., FNLA, MMP16, CDON, NRP2, PAX5, SULT1B1, L1CAM, SCHBP1) [77][78][79][80][81][82][83][84], in castration resistant prostate cancer (DPY19L2, NOVA1, NOVA2) [85,86] and in enzalutamide resistant (SLC6A15) [87] or androgen independent PCa cells (CALN1) [88]. They also expressed tumour suppressors (e.g., SULF1, EBF3) [89,90], many protocadherin family members, which have both suppressor and oncogenic roles in PCa [91], and solute carrier family members (e.g., SLC35F1, SLC26A2) implicated in drug uptake and efficacy modulation [92].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other metastatic sites for PCa, liver metastases reportedly have the highest fraction of genomic alterations and there are also potential liver specific alterations such as MYC amplification, PTEN deletion or PIK3CB amplification [ 33 ]. PCa may undergo site specific transcriptional changes, whereby the tumors adapt to survive and thrive in that specific micro-environment, and it may be that the changes in metabolism pathways are especially important to PCa that have located to the liver [ 38 , 39 ]. All three of these proteins have been linked with metabolism: PTEN with glycolysis and mitochondrial activity [ 40 ], MYC regulates genes involved in biogenesis of ribosomes and mitochondria, and glucose/glutamine metabolism [ 41 ], while PIK3CB is associated with metabolism of cholesterol, triglycerides, and sugars [ 42 , 43 ].…”
Section: Prostate Metastasis To the Livermentioning
confidence: 99%